Pengaruh Penggunaan E-Commerce dan Non E-Commerce terhadap Pendapatan Usaha Mikro, Kecil, dan Menengah (UMKM) di Desa Sukamahi, Kecamatan Cikarang Pusat - Faizal Muhamad; Ika Rediyana (AKUNTANSI 45, 2026)
The advancement of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt in managing their business activities, particularly in choosing appropriate sales platforms. E-commerce has emerged as a modern solution that helps business actors reach a wider and more efficient market. On the other hand, some MSMEs continue to rely on conventional (non ecommerce) methods for various reasons, such as limited access to technology or a preference for local market practices. This study aims to determine the influence of e-commerce and non e-commerce usage on the income of MSMEs in Sukamahi Village, Central Cikarang District, Bekasi Regency. This research employs a quantitative approach using a survey method by distributing questionnaires to 60 MSME respondents from a total population of 142 MSMEs registered with the local Department of Cooperatives and MSMEs. The data were analyzed through validity tests, reliability, normality, multicollinearity, heteroscedasticity, and multiple linear regression analysis. The findings show that both e-commerce and non e-commerce have a significant influence on MSME income. These two marketing strategies can be utilized in a complementary manner depending on the business characteristics and customer demands. Therefore, the results of this study are expected to serve as valuable input for MSME actors and policymakers in designing income enhancement strategies that integrate both digital and conventional approaches in a balanced and adaptive manner in response to technological developments and market changes.